ANTI-INFLAMMATORY EFFECT OF ZANTHOXYLUM BUNGEANUM-CAKE-SEPARATED MOXIBUSTION ON RHEUMATOID ARTHRITIS RATS - Lei, Xulu; Cheng, Shirui; Peng, Honglian; He, Qin; Zhu, Hongyu; Xu, Mengqian; Wang, Qinqin; Liu, Li; Zhang, Chengshun; Zhou, Qizhi; Ying, Jian; Zeng, Fang; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Zanthoxylum bungeanum-cake-separated moxibustion (ZBCS-moxi), a kind of traditional therapy of moxibustion, has been used in China since 340 B.C. However, its mechanism remains unclear. So, this study was attempted to reveal the anti-inflammatory effect of ZBCS-moxi on rheumatoid arthritis (RA) rats. Methods and Materials: Forty health SD female rats were randomly divided into 4 groups (n=10/group): control group, model group, Zanthoxylum bungeanum-cake-separated moxibustion group (ZBCS-moxi group) and Aconitum carmichaeli-cake-separated moxibustion group (ACCS-moxi group). RA model was induced by injecting 0.1 ml Freund’s complete adjuvant (FCA) into the right hind paw of rats. Eleven days after CFA injection, the rats in ZBCS-moxi group received Zanthoxylum bungeanum- cake-separated moxibustion on Shenshu (BL23), Zusanli (ST36) acupoints and the dorsum right hind paw respectively for 3 weeks. The ACCS-moxi group was used as a positive control, while the rats were treated with Aconitum carmichaeli-cake-separated moxibustion on the same acupoints and courses. After a 3-week treatment, we investigated anti-inflammatory effect by measuring the paw volume, observing the pathologic morphology of synovial membranes and detecting the concentration of IL-1β and TNF-α in serum. Results: Compared to model group, the swollen paw volumes, the synovial hyperplasia and pannus formation of synovial membranes and the concentration of IL-1β and TNF-α in serum decreased obviously (P<0.01, P<0.05) in ZBCS-moxi group, as well as in ACCS-moxi group. However, the swollen paw volumes, the synovial hyperplasia and pannus formation of synovial membranes and the concentration of IL-1β and TNF-α in serum in ZBCS-moxi and ACCS-moxi group did not show significant differences (P>0.05) Conclusions: ZBCS-moxi displays anti-inflammatory effect on RA rats via suppressing the expression of cytokines and has similar effect to ACCS-moxi.